LEARNING ENGLISH IDIOMS THROUGH ENGLISH MOVIES: AN EFFECTIVE MULTIMEDIA APPROACH (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2025)
Idioms represent one of the most challenging aspects of English for second-language learners because their meanings cannot always be deduced from their individual words. Traditional methods of memorizing idioms often fail to capture their cultural richness, pragmatic functions, and contextual nuance. This paper explores how English movies serve as a powerful tool for learning idiomatic expressions through authentic usage, emotional engagement, and repeated exposure. Using examples from nature-based idioms, animal metaphors, human-body expressions, and journey-related metaphors, the article demonstrates how films provide meaningful context that enhances comprehension and retention. The discussion highlights the cognitive benefits of audiovisual learning, the cultural insights embedded in idiomatic language, and practical strategies for incorporating movies into English language instruction. The analysis concludes that movies not only enrich learners’ linguistic competence but also deepen their cultural understanding and communicative confidence.